Hubungan Disiplin Kerja Terhadap Pelatihan dan Kualitas Pelayanan Pegawai Outsourcing Dinas Perhubungan Kota Surabaya - Perwira Negara, Muhammad Handito; Hesty Prima Rini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to identify and analyze the influence of work discipline and training on the service quality of outsourcing employees at the Department of Transportation in Surabaya. This study is associative and employs a quantitative approach. The sample size of this research is 65 employees, using a saturated sampling technique. Data collection was conducted through interviews and questionnaires. The analytical tool used is the Statistical Package for the Social Sciences (SPSS) version 25. The results of this study are: 1) training has a positive and significant effect on the service quality of outsourcing employees at the Department of Transportation in Surabaya, and 2) work discipline has a positive and significant effect on the service quality of outsourcing employees at the Department of Transportation in Surabaya.